Comparative assessment of the effects of DREADDs and endogenously expressed GPCRs in hippocampal astrocytes on synaptic activity and memory - Lee, Sophie H.; Mak, Aline; Verheijen, Mark H. G. (Frontiers in Cellular Neuroscience, 2023)
DREADDs have proven themselves as one of the key in vivo techniques of modern neuroscience, allowing for unprecedented access to cellular manipulations in living animals. With respect to astrocyte research, DREADDs have become a popular method to examine the functional aspects of astrocyte activity, particularly G-protein coupled receptor (GPCR)-mediated intracellular calcium (Ca2+) and cyclic adenosine monophosphate (cAMP) dynamics. With this method it has become possible to directly link the physiological aspects of astrocytic function to cognitive processes such as memory. As a result, a multitude of studies have explored the impact of DREADD activation in astrocytes on synaptic activity and memory. However, the emergence of varying results prompts us to reconsider the degree to which DREADDs expressed in astrocytes accurately mimic endogenous GPCR activity. Here we compare the major downstream signalling mechanisms, synaptic, and behavioural effects of stimulating Gq-, Gs-, and Gi-DREADDs in hippocampal astrocytes of adult mice to those of endogenously expressed GPCRs.